Origin of Red Emission in β‐Ga2O3 Analyzed by Cathodoluminescence and Photoluminescence Spectroscopy. Issue 2 (3rd November 2020) - Naresh-Kumar, Gunasekar; MacIntyre, Hazel; Subashchandran, Shanthi; Edwards, Paul R.; Martin, Robert W.; Daivasigamani, Krishnamurthy; Sasaki, Kohei; Kuramata, Akito
Abstract : The spectroscopic techniques of cathodoluminescence (CL) and photoluminescence (PL) are used to study the origin of red emission in β‐Ga2 O3 grown using the edge‐defined film‐fed grown (EFG) method and hydride vapor phase epitaxy. Room‐temperature CL shows red emission peaks from samples doped with Fe, Sn, and Si and from unintentionally doped (UID) samples. Narrow emission lines around 690 nm are seen strongly in the Fe and UID samples. Temperature‐dependent PL analysis of the two prominent red emission lines reveals properties similar to the R lines in sapphire for all samples but with different levels of emission intensities. These lines are attributed to Cr 3+ ionic transitions rather than Fe 3+, as reported previously. The most likely origin of the unintentional Cr incorporation is the source material used in the EFG method. Abstract : This spectroscopic study investigates the origin of red emission in β‐Ga2 O3, which is extrinsic and is due to transition or rare earth metal dopants. In particular, the narrow peaks at 688 nm and 695 nm are due to Cr 3+ ions, and doping with Fe enhances red emission, whereas Sn quenches red emission intensities.